Konsep Kesejahteraan pada Masa Islam Klasik Dan Masa Modern - Ifa Afida (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2020)
The problem faced by developing countries is the welfare of their citizens. Welfare has become an important part of a country. Even the establishment or formation of a country is in order to realize the welfare of its people. Various ways, methods, rules, tools, approaches or policies have been chosen and carried out by a country in order to achieve these goals. Islam has a much better welfare concept than western economic concepts. The concept has also been implemented well from the time of the Prophet to the successor caliphs. Welfare in the view of Islam is not only assessed by material measures, but also by non-material measures such as the fulfillment of spiritual needs, maintenance of moral values ​​and the realization of social harmony. In this article, the author tries to describe the concept of well-being in the classical Islamic era and well-being in the modern period, whether in practice it has suffered a setback or progress, or both are running the same and balanced based on their particular characteristics.